2020
DOI: 10.1128/mbio.01527-20
|View full text |Cite|
|
Sign up to set email alerts
|

A Genome-Based Model to Predict the Virulence of Pseudomonas aeruginosa Isolates

Abstract: Variation in the genome of Pseudomonas aeruginosa, an important pathogen, can have dramatic impacts on the bacterium’s ability to cause disease. We therefore asked whether it was possible to predict the virulence of P. aeruginosa isolates based on their genomic content. We applied a machine learning approach to a genetically and phenotypically diverse collection of 115 clinical P. aeruginosa isolates using genomic information and corresponding virulence phenotypes in a mouse model of bacteremia. We defined the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
(101 reference statements)
3
8
0
Order By: Relevance
“…Additionally, we saw the spread of the SPLT isolates throughout the phylogenetic tree based on core genes, still showing patient specific clustering. This observation was found to be coherent with the noted difficulties in discriminating CF isolates based on their geography and origin ( Jeukens et al, 2019 ; Pincus et al, 2020 ).The latter demands further understanding of the emergence of resistance and virulence among these P. aeruginosa to avoid or manage lung infections ( Cho et al, 2014 ; Jaillard et al, 2017 ).…”
Section: Discussionsupporting
confidence: 64%
“…Additionally, we saw the spread of the SPLT isolates throughout the phylogenetic tree based on core genes, still showing patient specific clustering. This observation was found to be coherent with the noted difficulties in discriminating CF isolates based on their geography and origin ( Jeukens et al, 2019 ; Pincus et al, 2020 ).The latter demands further understanding of the emergence of resistance and virulence among these P. aeruginosa to avoid or manage lung infections ( Cho et al, 2014 ; Jaillard et al, 2017 ).…”
Section: Discussionsupporting
confidence: 64%
“…By including these features in our prediction models, we noted a moderate increase across all the measured metrics relative to using only AmpliSeq data. These results are in line with previous studies showing the improvement of ML-based phenotype prediction by adding relevant clinical data (MacFadden, Melano et al 2019, Pincus, Ozer et al 2020). We note that clinical factors only modestly improved the performance of the models (∼5%), highlighting the rich information and predictive value of the Pa AmpliSeq data alone.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that genetic variation in dominant pathogens can significantly complement and improve upon predictions of disease status based on the microbiome. Along these lines, another recent study showed that the Pa genomic data can predict pathogenicity in mouse models (Pincus, Ozer et al 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Machine learning analyses were performed on the ST258 CR-Kp isolates ( n = 123) using the sci-kit learn library (v0.23.2) ( https://www.jmlr.org/papers/v12/pedregosa11a.html ) in Python v3.6.12 following the pipeline described by Pincus et al ( 58 ) For the curated analysis, β-lactamase presence/absence, outer membrane porin phenotype, transposon isoform, and bla KPC copy number were used as features and converted to binary variables. For example, bla KPC copy number was considered “high” if ≥ 4 copies were present and “low” if < 4 copies were present.…”
Section: Methodsmentioning
confidence: 99%